Comidas en puré para problemas al tragar - Wendy J. Dahl (EDIS, 2011)
Although we all enjoy puréed foods as a part of a healthy diet, puréed diets may be recommended for frail older adults who have chewing and/or swallowing problems. This 4-page Spanish-language fact sheet describes reasons to prepare puréed foods and tips for preparing and serving great tasting and ready to swallow puréed foods. Written by Wendy J. Dahl and published by the UF Department of Food Science and Human Nutrition, May 2011.